ANALISIS PENGENDALIAN PERSEDIAAN BUKU BERBASIS TEKNOLOGI INFORMASI UNTUK MENINGKATKAN KINERJA KEUANGAN PT. GRAMEDIA REGIONAL JAWA TIMUR, JAWA TENGAH, BALI - Alanda, Erick (Program Doktor Ilmu Ekonomi, 2009)
Inventory controlling comprise very important activity and should be performed by a company, cause this inventory a important investment and sensitive on market price decline, stealing, wasting, destruction and cost exceed as result of inexact of supervision on those inventory. Similarly, Gramedia Bookstore, in their activity to fulfill people needs on reading materials, Gramedia Bookstore held controlling activity on inventory which supported by data process using information technology that is computer, then those need on inventory will be completed good and controlled.In this thesis writing, the writer do research in Gramedia Bookstore under East Java, Central Java and Bali areas, get along with problem examined â€œControlling Analysis Book Inventory Information Technology-Based to Improving Financial Performance PT. Gramedia East Java central Java and Bali Regionsâ€.Research methodology by writer used are quantitative descriptive method, which data gained during this research, are processed, analysed and deepen processed with aim to testing variable X and Y roles.Data used are primary and secondary data, gained through field research by observation, interview and questionnaire in research object. Quantitative analysis used in this research are multivariate analysis by PLS (Partial Least Square) method.Research had done in Gramedia Bookstore could be explained if cooperation with publisher good engaged in order to influencing inventory control system, if sales growth increase then financial performance will be increase and otherwise sales growth decline means financial performance decline. Merchandise inventory control by using information technology could be aid the control processing on merchandise inventory done quicker, with more accurate yield as well as data storage be better and electronic data processing could be diminishing related employees tasks burden, until Gramedia Bookstore secure inventory information quicker and accurate as well as could be distributing information to whom it may concern on time.Keywords: EOQ, Safety Stock, Partial Least Square.